Cultural management and policy in Latin America - Henze, Raphaela; Escribal, Federico (London ; New York : Routledge, Taylor & Francis Group, 2021)
"Cultural Management and Policy in Latin America provides in-depth insights into the education and training of cultural managers from interdisciplinary and comparative perspectives. The book focuses on the effects of neoliberalism on cultural policies across the region, and questions how cultural managers in Latin America deal not only with contemporary political challenges but also with the omnipresent legacy of colonialism. In doing so, it unpacks the methods, formats, and narratives employed. Reflecting on emerging and contemporary research topics, the book analyses the key literature and scholarly contexts to identify impacts in the region and beyond. The volume provides scholars, students and reflective practitioners with a comprehensive resource on international cultural management that helps to overcome Western-centric methods and theories"--
OCLC-licensed vendor bibliographic record.
Keywords: International business enterprises -- Management -- Social aspects -- Latin America; Management -- Latin America; Corporate culture -- Latin America; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities